2015
DOI: 10.5935/0004-2749.20150072
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery alone cannot be considered an IOP-lowering procedure for open-angle glaucoma patients: an evidence-based perspective

Abstract: Due to the significant coexistence of cataract and glaucoma, cataract surgery has become a routine procedure in a glaucoma surgeon's practice (1)(2)(3)(4) . The indication of cataract surgery in glaucoma patients usually differs from that in ordinary cases, either because of the intraoperative technique and perioperative care or because of the expected results. The approach also varies significantly among patients with glaucoma, depending on various factors such as disease stage, preoperative intraocular press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In rigorous studies, the mean long-term changes in IOP value ranged from 1.5 and 2 mmHg. However, whether this percentage reduction in IOP is clinically meaningful remains unclear (21) , also considering that no statistically significant reduction in the number of eye drops was found.…”
Section: Discussionmentioning
confidence: 97%
“…In rigorous studies, the mean long-term changes in IOP value ranged from 1.5 and 2 mmHg. However, whether this percentage reduction in IOP is clinically meaningful remains unclear (21) , also considering that no statistically significant reduction in the number of eye drops was found.…”
Section: Discussionmentioning
confidence: 97%
“…Prata et al . [ 22 ] showed that 40% of glaucoma patients lost IOP control during the first year after cataract surgery. Similar results were demonstrated by Shingleton et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, more IOP decrease was acquired in group 2 at postoperative status. In the interim, Prata et al [22] . detailed that cataract surgery procedure could decrease IOP during the first few days after phacoemulsification procedure.…”
Section: Discussionmentioning
confidence: 99%